Analisis Pertumbuhan dan Perubahan Struktur Ekonomi di Provinsi Sulawesi Tengah Tahun 2018 - 2022 - Bayu Dwi Cahya Pelealu; Herwin Mopangga; Irawati Abdul (Masyarakat Ekonomi Syariah Bogor, 2024)
A country's continuous rise towards improvement over a certain period of time is the process of economic growth. The elements that make up a country's economic structure function to regulate a country's household and are referred to as the economic structure: household, business, government, economic system, input market, and output market. The economics of each of these parts is different. Input markets (for goods and services), output markets (for households, businesses, governments, and economic systems) are components of the economy. This research aims to find out how much economic growth there has been and whether there has been a change in the economic structure of Central Sulawesi Province in the 2018-2022 period. The research uses quantitative research methods, using secondary data, obtained through PDRB Data for Central Sulawesi Province. Analysis methods include Location Quontien (LQ) Analysis and Structural Checks Index (SCI) Analysis. The research findings indicate that from 2018 to 2022, Central Sulawesi Province experienced significant shifts, identifying five key sectors that dominated economic growth. The mining and quarrying sector, along with the processing industry, served as the primary drivers, while the agriculture, forestry, and fishery sectors showed important contributions despite fluctuations. The water supply and waste management sector, although its contribution was low, exhibited stable growth, and the government administration sector also positively contributed with consistent growth. Thus, it can be concluded that there has been a structural change in the economy of Central Sulawesi over this five-year period. The secondary sector has emerged as a driving force behind the economic structural changes in the region, as indicated by an increase in the Sectoral Contribution Index (SCI) year by year, despite declines in the primary and tertiary sectors. This change reflects a shift in resource allocation increasingly directed toward the secondary sector as the main pillar of the regional economy.